2013
DOI: 10.1371/journal.pone.0078339
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Kinase Receptor ROR1 Is Constitutively Phosphorylated in Chronic Lymphocytic Leukemia (CLL) Cells

Abstract: Phosphorylation of receptor tyrosine kinases (RTKs) has a key role in cellular functions contributing to the malignant phenotype of tumor cells. We and others have previously demonstrated that RTK ROR1 is overexpressed in chronic lymphocytic leukemia (CLL). Silencing siRNA downregulated ROR1 and induced apoptosis of CLL cells. In the present study we analysed ROR1 isoforms and the phosphorylation pattern in CLL cells (n=38) applying western blot and flow-cytometry using anti-ROR1 antibodies and an anti-phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 42 publications
4
65
1
Order By: Relevance
“…High ROR1 phosphorylation intensity was found in progressive compared to non-progressive CLL. The same pattern was observed in other malignancies including breast, lung and ovarian cancer cells with an aggressive course (21). Furthermore, ROR1 expression at the protein level was significantly higher in aggressive tumors (15).…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…High ROR1 phosphorylation intensity was found in progressive compared to non-progressive CLL. The same pattern was observed in other malignancies including breast, lung and ovarian cancer cells with an aggressive course (21). Furthermore, ROR1 expression at the protein level was significantly higher in aggressive tumors (15).…”
Section: Introductionsupporting
confidence: 78%
“…The number of ROR1 receptors on the surface of CLL cells was estimated to be in the range of 10,000/cells, which are sufficient to be targeted by monoclonal antibodies (21). ROR1 expression during CLL becomes further increased during disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…23 To date, high-level expression of ROR1 has been found to have adverse prognostic significance for patients with breast cancer, [24][25][26][27] ovarian cancer, 28,29 melanoma, 30 or Ewing sarcoma. 31 Moreover, high-level expression of ROR1 also has been associated with higher levels of AKT activation, 24,30,32,33 consistent with the notion that ROR1 signaling leading to activation of AKT may serve as a driver, not just in CLL, but also in other malignancies. Because of this and its restricted postpartum expression, ROR1 may be an attractive target for therapy with either mAbs, 7,34 or other agents that specifically inhibit this orphan receptor and/or its downstream signaling pathways.…”
Section: Discussionsupporting
confidence: 60%
“…Other variants are 260 kDa that is attributed to dimerized ROR1 detected in a large number of patients and 64 kDa as a truncated intracellular part of ROR1. Moreover, 64, 105 and 130 kDa variants were constitutively phosphorylated with progressive disease having significantly higher intensity of phosphorylation of the 130 kDa band compared with non-progressive cases, though no association was found between different ROR1 isoforms and disease progression [70].…”
Section: Ror1 Expression In Hematological Malignancies and Solid Tumorsmentioning
confidence: 84%
“…A longitudinal follow-up of CLL subjects showed that in non-progressive patients ROR1+ cells remained stable over time; however with disease progression their number increased [71]. Besides, higher phosphorylation of ROR1 protein was observed in progressive versus non-progressive CLL [70]. Interestingly, in sera of CLL patients, anti-ROR1 Abs are not detected; however vaccination of patients with CD40L-expressing autologous tumor cells leads to production of anti-ROR1 Abs.…”
Section: Ror1 Expression In Hematological Malignancies and Solid Tumorsmentioning
confidence: 99%